Mercury(II) coordination polymers based on aniline-substituted tetra pyridyloxy cyclotriphosphazene: Syntheses, characterizations and UV–Vis absorption properties. (15th November 2019) - Davarcı, Derya; Şenkuytu, Elif; Zorlu, Yunus
Graphical abstract: A new ligand and two mercury(II) cyclotriphosphazene coordination polymers have been synthesized and their crystal structures, thermal behaviors and UV properties determined. Abstract: Dianiline-tetrapyridyloxy-cyclotriphosphazene (AnPyCp ), as a novel flexible molecular building block, and its mercury(II) coordination polymers were successfully synthesized. The isolated crystalline coordination polymers, formulated as [Hg(AnPyCp)(Cl)2 ]·CH3 CN n (1 ) and [Hg2 (AnPyCp)(I)4 ]·CH3 CN n (2 ), were structurally characterized by elemental analysis, FT-IR spectroscopy and single crystal X-ray crystallography. Furthermore, the X-ray crystal structure analysis revealed that complexes 1 and 2 crystallize in the triclinic crystal system with the P 1 ¯ space group. In complexes 1 and 2, AnPyCp exhibited κ 2 N and κ 3 N coordination binding modes with the divalent Hg ions to form 1D chain structures. The central Hg 2+ ion in complexes 1 and 2 has a distorted tetrahedral geometry. The UV–Vis properties and thermal stability of AnPyCp and its complexes (1 and 2 ) were also investigated. UV–Vis experiments, including titration and continuous variation (Job's plot analysis), showed that all of the spectrophotometric properties in the solution state support the crystal structures of the complexes. According to TGA analysis, the coordination polymers exhibited thermal stability up to ∼230 °C, however AnPyCp showed a greater thermal stability than 1 and 2 .